Msh4 and Msh5 Function in SC-Independent Chiasma Formation During the Streamlined Meiosis of Tetrahymena. Issue 3 (11th September 2014) - Shodhan, Anura; Lukaszewicz, Agnieszka; Novatchkova, Maria; Loidl, Josef
Abstract: ZMM proteins have been defined in budding yeast as factors that are collectively involved in the formation of interfering crossovers (COs) and synaptonemal complexes (SCs), and they are a hallmark of the predominant meiotic recombination pathway of most organisms. In addition to this so-called class I CO pathway, a minority of crossovers are formed by a class II pathway, which involves the Mus81-Mms4 endonuclease complex. This is the only CO pathway in the SC-less meiosis of the fission yeast. ZMM proteins (including SC components) were always found to be co-occurring and hence have been regarded as functionally linked. Like the fission yeast, the protist Tetrahymena thermophila does not possess a SC, and its COs are dependent on Mus81-Mms4. Here we show that the ZMM proteins Msh4 and Msh5 are required for normal chiasma formation, and we propose that they have a pro-CO function outside a canonical class I pathway in Tetrahymena . Thus, the two-pathway model is not tenable as a general rule.